Redefiniciones: Los Otros góticos - Marta Sierra (Mistral, 2021)
This article addresses a redefinition of the Gothic genre as a “Red Gothic,” a term that I coin to define the visceral traits of literary and artistic productions of the “horror” genre in Latin America. I center on the works of Mariana Enríquez, placing them in dialogue with those of visual artists Ana Mendieta and Teresa Margolles. This is an initial proposal for further discussion on political uses of the Gothic in Latin America. In response to the violence and discrimination produced by different implementations of Neoliberalism in the region, a growing field of artists and writers work with Gothic imagery in a flexible, hybrid way to create new representations of “monsters” and “cannibals.” By looking at feminist critiques on post-humanism and cyborg identities (Rosi Braidotti, Donna Haraway), I propose that “Red Gothic” embodies those gaps and erasures of different populations that still claim a place in Latin American societies.